Comprehensive dental examination and management of a patient with X-linked hypophosphatemic rickets (Эндодонтия Today, 2020)
One of the main findings in patients with known hypophosphataemic rickets (XLHR) is multiple abscesses or sinus tracts associated with carious free teeth of the primary and the permanent dentition. Such a complication is usually detected too late, when it is not possible to preserve the causative tooth due to the destruction of a large volume of the alveolar bone or the risk of damage to the permanent tooth germ. A 10-year old female with genetically and biochemically confirmed XLHR was examined at the Paediatric Dentistry Department of A. I. Yevdokimov MSUMD. Abnormalities typical of XLHR patients and clinically hidden lesions of her teeth were revealed by using modern radiation diagnostic methods. The comprehensive dental examination made it possible to provide timely dental care to the patient.